Bank BRI Digital Transformation Strategy for Corporate QLola Application Decision-Making - Syafaruddin, Frans Prayuda; Wibowo, Wisnu Aji; Indriani, Farida (LifeSciFi, 2025)
This study examines the digital transformation strategy of Bank Rakyat Indonesia (BRI) in fostering corporate decision-making towards the adoption of the QLola application for business transactions. In response to rapid technological advancements and shifting customer behavior towards digital financial services, BRI launched the QLola platform as an integrated corporate digital banking solution. This research employs a qualitative approach, utilizing in-depth interviews and triangulation techniques with corporate users across various industries, including hospitality, seafood export, and agriculture sectors. The findings reveal that BRI's strategic focus on comprehensive digital transformation, including API integration and data-driven decision dashboards, has significantly enhanced corporate transaction efficiency and financial management transparency. Additionally, the study underscores that BRI's digital banking innovation not only strengthens its position in corporate banking services but also contributes to building a more inclusive and competitive national digital financial ecosystem. The novelty of this research lies in its emphasis on the correlation between digital banking transformation strategies and corporate decision-making processes, providing valuable insights for practitioners and academics in understanding the dynamics of digital financial services adoption.